Reducing suffering in experimental autoimmune encephalomyelitis (EAE). - Wolfensohn, S; Hawkins, P; Lilley, E; Anthony, D; Chambers, C; Lane, S; Lawton, M; Voipio, H; Woodhall, G (2013)
This report is based on discussions and submissions from an expert working group consisting of veterinarians, animal care staff and scientists with expert knowledge relevant to the field. It aims to facilitate the implementation of the Three Rs (replacement, reduction and refinement) in the use of animal models or procedures involving experimental autoimmune encephalomyelitis (EAE), an experimental model used in multiple sclerosis research. The emphasis is on refinement since this has the greatest potential for immediate implementation. Specific welfare issues are identified and discussed, and practical measures are proposed to reduce animal use and suffering. Some general issues for refinement are summarised to help achieve this, with more detail provided on a range of specific measures to reduce suffering.